Efeito de uma sessão aguda de exercício físico aeróbio sobre marcadores de inflamação e biomarcadores de função renal - Pinto, Walter Pereira (2018)
The inflammation is common and a risk factor to mortality in patients with chronic kidney disease (CKD). The use with some drugs has been used to diminish this inflammatory state. However, aerobic exercise has been described to modulate the inflammatory response. Thus, the present study evaluated the effect of an acute aerobic exercise session on biomarkers of inflammation and renal function in patients with non-dialytic CKD. MATERIALS AND METHODS: 10 subjects with CKD and 10 subjects with normal renal function performed experimental sessions of aerobic exercise on a cycle ergometer for 45 min, 50% at VO2 peak. Before and after the exercise session, blood samples were collected for the analysis of inflammatory and renal function biomarkers. Data were compared using the general linear model (GLM) test for repeated measures and Pearson's correlations were used to evaluate the association between the variables before and after the exercise session. RESULTS: After an aerobic exercise session, IL-10 levels increased in both groups, mainly in CKD patients (p <0.0001). Before exercise, we observed a positive association between IL-6 with Cystatin-C, and NGAL (p = 0.006). TNF-alpha correlated positively with Cystatin-C and NGAL only after exercise (p = 0.001). CONCLUSION: The present study confirmed a positive association between biomarkers of renal function and inflammation. In this study, an acute aerobic exercise session was able to increase IL-10 levels in CKD patients, suggesting that physical exercise may contribute to an anti-inflammatory response. However, it is necessary that this hypothesis be confirmed with a larger number of patients with CKD.